What happens next - Swinarski, Claire (Quill Tree Books, an imprint of HarperCollins Publishers, 2021)
"It's summer in Moose Junction, and twelve-year-old Abby McCourt should be excited about the approaching solar eclipse--especially because she's obsessed with astronomy--but she's not. After the incident at the Memorial Day barbecue, nothing has been the same. Her friends avoid her. Her parents are stressed. And the one person she felt closest to--her older sister Blair--has been sent to a treament facility to learn how to eat again. But wait . . . rewind a bit. This didn't really start with Blair's meltdown over a cupcake at the barbecue. When Abby thinks on it, she can see traces of her sister's eating disorder from years back. She just never imagined it would get this bad. Then world-renowned astronomer Dr. Leo Lacamoire arrives in town on a mission to find a telescope that was stolen from him and employs Abby's help. Together, they hatch a plan that might be able to get them both what they want--a way to heal what the past has broken"--Provided by publisher.